About Some Phonostylistic Features of Amateur Speech - Soliyeva Mahliyo; Xikmatullo Do’stmatov (Zien Journals, 2023)
In this article, an opinion is expressed about the phonetic phenomena in the speech of amateurs, the stylistic possibilities that emerge as a result of this phenomenon. The article describes the importance of phonostylistic tools in creating meaning, their methodological aspects related to their use in comic texts.
Keywords: phonostylistic tool; communicative purpose